Luteolin promotes mitochondrial protection during acute and chronic periods of isoproterenol induced myocardial infarction in rats - Murugesan Madhesh; Manju Vaiyapuri (The Egyptian Heart Journal, 2013)
Objective: An attempt has been made to evaluate the mitochondrial protection in acute and chronic periods after isoproterenol (ISO)-induced myocardial-infarction (MI) in male Wistar rats. Materials and methods: Luteolin was supplemented by intra-gastric intubation at a daily dose of 0.3 mg/kg body weight for 30 days. In the acute MI model, luteolin had been administered once per day to rat groups during 30 days. On 29th and 30th days, the rats of the acute MI control groups were administered 85 mg/kg body weight, isoproterenol, intra-peritoneally at an interval of 24 h. In the chronic MI model luteolin was supplemented to the rat group during 30 days. On the 1st and 2nd days, the rats of the chronic MI control and luteolin treatment groups were administered ISO by the same way. Results: The isoproterenol-treated rats both in acute and chronic models showed an increase in the level of TBARS and a decrease in the activities of mitochondrial antioxidants in MI rats, an increase in levels of mitochondrial lipid profile except phospholipids and the activities of mitochondrial enzymes were decreased in isoproterenol-treated rats. Oral treatments with luteolin in both acute and chronic models showed a significant decrease in the levels of mitochondrial lipid peroxidation, increase in the mitochondrial antioxidant levels and also decrease in the mitochondrial enzymes. Conclusion: Thus the present study revealed that luteolin ameliorates mitochondrial damage in isoproterenol induced myocardial infarction by maintaining lipid peroxidation metabolism due to its free radical scavenging, mitochondrial lipids, antioxidants and mitochondrial enzymes. Histopathological observations were also in correlation with the biochemical parameters.